Case control study: magnetic resonance spectroscopy of brain in HIV infected patients. Issue 1 (December 2016) - Bairwa, Devender; Kumar, Virendra; Vyas, Surabhi; Das, Bimal; Srivastava, Achal; Pandey, Ravinder; Sharma, Surendra; Jagannathan, Naranamangalam; Sinha, Sanjeev
Abstract Background In vivo proton magnetic resonance spectroscopy (1 H-MRS) studies on brain in HIV infected patients have shown significant alteration in neuro-biochemicals. Methods In this study, we measured the neuro-biochemical metabolites from the left frontal white matter (FWM) and left basal ganglia (BG) caudate head nucleus in 71 subjects that include 30 healthy controls, 20 asymptomatic HIV and 21 HIV patients with CNS lesion. Proton MR spectra were acquired at 3 T MRI system and the concentration (institutional units) of tNAA (N-acetylaspartate, NAA + N-acetylaspartylglutamate, NAAG), tCr (Creatine, Cr + phosphocreatine, PCr), choline containing compounds (tCho), glutamate + glutamine (Glx) and lipid and macromolecules at 0.9 ppm were determined using LC Model. Results In BG, the concentration of tNAA (6.71 ± 0.64) was decreased and in FWM, the concentration of Glx (20.4 ± 7.8), tCr (9.14 ± 3.04) and lipid and macromolecules at 0.9 ppm (8.69 ± 2.96) were increased in HIV patients with CNS lesion. In healthy controls, the concentration of tNAA in BG was 7.31 ± 0.47 and concentration of Glx, tCr and lipid and macromolecules in FWM were 15.0 ± 6.06, 6.95 ± 2.56, 5.59 ± 1.56, respectively. Conclusion Reduced tNAA in BG suggests neuronal loss in HIV patients with CNS lesion while increased Glx in FWM may suggest excito-toxicity. In addition, increased levels of tCr in FWM of HIV patients were observed. The study indicates region specific metabolic changes in tNAA, tCr and Glx in brain of HIV infected patients.